EVALUASI KEBUGARAN JASMANI MELALUI HARVARD STEP TEST PADA MAHASISWA PENJASKESREK FKIP UNIVERSITAS ABULYATAMA - Zainuddin, Zainuddin; Syahrinursaifi, Syahrinursaifi; Musran, Musran; Zaki, Ammar (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Physical fitness is the body's ability to perform an activity without feeling excessive fatigue. Students in following a series of lectures have not shown good physical fitness performance. The effort made is to evaluate physical fitness through the Harvad step test. So that students can improve their training and detect their own fitness level. The purpose of this study was to evaluate physical fitness through the Harvard step test on physical education students health and recreation Faculty of Teacher Training and Education Abulyatama. This type of research is evaluative with a quantitative descriptive approach. Collecting data for this study through the Harvard step test. The population and sample of this study were 30 students of Physical Education Health and Recreation class 2022. The results showed physical fitness through the Harvard step test with an average of 33.47 (very poor), with the following details: 1) Moderate category with a frequency of 1 student (3.33%), 2) Less category with a frequency of 2 students (6.67%), and 3) Very less category with a frequency of 27 students (90.00%). The research concluded that the evaluation of physical fitness through the Harvard step test on students of physical education health and recreation of the Faculty of Teacher Training and Education Abulyatama was in the category of very poor